In adults: 47.2% have periodontitis! How about in orthodontic patients? Em adultos: 47,2% apresentam periodontite! E nos pacientes ortodônticos? - Alberto Consolaro (Dental Press Editora, 2013)
The occurrence of chronic inflammatory periodontal disease due to dental plaque in adults over 30 years of age was noticed in 47.2% of the 3,742 subjects studied, representing a 64.7 million people population in the 50 states of the U.S. and the District of Columbia. The methods used by the authors were uniquely precise and the results brought us to great insight on the correlation between orthodontic treatment and periodontal health, which is described below. A prevalência de 47,2% da doença periodontal inflamatória crônica induzida pela placa dentobacteriana em adultos com mais de 30 anos foi detectada em 3.742 adultos, que representaram estatisticamente 64,7 milhões de pessoas de 50 estados e do distrito federal dos Estados Unidos da América. O método foi preciso e os resultados induzem a alguns insights quanto à relação entre o tratamento ortodôntico e a saúde dos tecidos periodontais, que foram expostos no texto desse trabalho.